Assessing static balance control improvement following cataract surgery using a smartphone - Lorrana de Souza Azevedo; Newton Quintino Feitosa; Enzo Gabriel Rocha Santos; Márcio Augusto Moraes Alvarez; Lucciano Augusto Ximenes Norat; Gabriel Izan Santos Botelho; Anderson Belgamo; Gustavo Henrique Lima Pinto; Ketlin Jaqueline Santana Castro; Bianca Callegari; Anselmo de Athayde Costa e Silva; Raílson Cruz Salomão; et al. (Digital Health)
Introduction Cataract remains a prevalent cause of visual impairment among the elderly, significantly increasing the risk of falls due to compromised visual function. Cataract removal surgery has been established as a means to enhance visual acuity and balance control. The advent of novel technologies, such as accelerometers integrated into smartphones, provides an opportunity to assess static balance control. We compared static balance measurements obtained from accelerometer built-in smartphones before and after cataract removal surgery. Methods Our sample comprised 29 individuals diagnosed with bilateral cataracts scheduled for cataract removal surgery. We evaluated participants’ visual acuity and recorded their body oscillations using the smartphone's embedded accelerometer during static balance maintenance, both with eyes open and closed, before and after surgery. We compared quantitative parameters of static balance evaluation at both time points. Results A significant improvement in visual acuity following cataract removal surgery was observed. Moreover, under open-eye conditions, all quantitative parameters of static balance evaluation exhibited significant improvement, with only one parameter showing improvement under closed-eye conditions. Conclusion Inertial sensors integrated into smartphones serve as practical tools for monitoring changes in static balance control resulting from cataracts, as well as for evaluating balance recovery after lens extraction surgery.